Contraception : herbal and modern strategies - Nurul Ain KB,; Irfan Y,; Mahanem Mat Noor, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Population explosion is one of the global issues of concern. The increasing number of individuals could result in negative impact on social and economy. To overcome this problem, convenient and safe modern contraception was introduced. However, recently many researchers have conducted studies on the effectiveness of medicinal plants as contraceptive agents on human and animal models. Therefore, the studies of herbal and modern contraceptives were summarized in this review article. A total of 66 relevant articles were documented having information regarding the modern and herbal contraceptives. All contraceptives are highly effective provided they are used consistently and in the proper way. Contraception is important as it could prevent diseases and infections caused by sexual intercourse and prevent unintended pregnancy. Therefore, this review is an attempt to summarize the potential of medicinal plants as contraceptive agents and the modern contraceptive methods used as birth control in males and females.